Myrcene and terpene regulation of TRPV1. Issue 1 (1st January 2019) - Jansen, C.; Shimoda, L.M.N; Kawakami, J.K.; Ang, L.; Bacani, A.J.; Baker, J.D.; Badowski, C.; Speck, M.; Stokes, A.J.; Small-Howard, A.L.; Turner, H
ABSTRACT: Nociceptive Transient Receptor Potential channels such as TRPV1 are targets for treating pain. Both antagonism and agonism of TRP channels can promote analgesia, through inactivation and chronic desensitization. Since plant-derived mixtures of cannabinoids and the Cannabis component myrcene have been suggested as pain therapeutics, we screened terpenes found in Cannabis for activity at TRPV1. We used inducible expression of TRPV1 to examine TRPV1-dependency of terpene-induced calcium flux responses. Terpenes contribute differentially to calcium fluxes via TRPV1 induced by Cannabis -mimetic cannabinoid/terpenoid mixtures. Myrcene dominates the TRPV1-mediated calcium responses seen with terpenoid mixtures. Myrcene-induced calcium influx is inhibited by the TRPV1 inhibitor capsazepine and Myrcene elicits TRPV1 currents in the whole-cell patch-clamp configuration. TRPV1 currents are highly sensitive to internal calcium. When Myrcene currents are evoked, they are distinct from capsaicin responses on the basis of Imax and their lack of shift to a pore-dilated state. Myrcene pre-application and residency at TRPV1 appears to negatively impact subsequent responses to TRPV1 ligands such as Cannabidiol, indicating allosteric modulation and possible competition by Myrcene. Molecular docking studies suggest a non-covalent interaction site for Myrcene in TRPV1 and identifies key residues that form partially overlapping Myrcene and Cannabidiol binding sites. We identify several non- Cannabis plant-derived sources of Myrcene and other compounds targeting nociceptive TRPs using a data mining approach focused on analgesics suggested by non-Western Traditional Medical Systems. These data establish TRPV1 as a target of Myrcene and suggest the therapeutic potential of analgesic formulations containing Myrcene.